Professionalism of Teachers Akidah Akhlaq in Utilizing Digital-Based Learning Media At MAUWH - Mohammad Saat Ibnu Waqfin; Mukhamad Tarno (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to determine the professionalism of teachers in the akidah akhlaq subject in utilizing digital technology in learning that currently exists in pandemic conditions or the new normal period. The method used by researchers in this case is qualitative descriptive analysis. The subjects of this study were informants who provided data through interviews. The informants in this study were the time curriculum and of course the teachers who taught the subject of akidah akhlaq at MA Unggulan KH. Abdul Wahab Hasbulloh (MAUWH) Tambakberas Jombang. The data analysis used in this research is descriptive analysis. This study resulted in the findings that the professionalism of teachers in the use of digital learning media is quite professional and disciplined even in pandemic conditions and online learning. The teachers still do the job and cover all professional teacher competencies from Pedagogic Competencies, Personality Competencies, Social Competencies, and Professional Competencies. Teachers are still guided and given direction when starting distance learning. Facilitating everything needed by teachers and students so that learning continues effectively. The advantages of learning using digital media are that regardless of the conditions and the learning time, it will still be carried out and makes it easier for teachers and students. There are deficiencies in learning akidah morals that uphold affective aspects that are not applicable. The main obstacles and barriers lie in students who lack interest in responding to learning, and limited signal and inadequate cell phones.